Implementing Picture Series to Enhance The Vocabulary of The Eight Grade Students of SMP Negeri 3 Parepare - Umi Kamaruddin (La Parole : Journal of Language Teaching and Pedagogy, 2020)
Picture is kind of interesting visual aid which is able to give motivation and good impression for the students, so that the students can memorize the words related to the picture. Because of that, it is important to find out the solution to enhance students’ vocabulary. The objective of the research are to find out whether the use of picture series is able to enhance the vocabulary of the eighth grade students of SMP Negeri 3 Parepare. This research used quasi-experimental design with two groups namely pre-test and post-test. The population of this research were the eighth grade students of SMP Negeri 3 Parepare Gasal semester in Academic 2018/2019 with sample taking technique which was clustering random sampling consisted of 54 students from two classes taken from the eighth grade population, where class VIII.7 was an experimental class and VIII.9 as a control class. The results showed that the learning process using picture series could improve students' vocabulary skills, based on the results of research in chapter IV it was known that the average score of learning outcomes before applied picture series of a pre-test (66.70) of the standard score of DEPDIKNAS 2015 with Learning outcomes category is in the low category. After applying picture series, the researcher obtained the results of the average score of students in the post-test, namely (86.62). Based on data analysis through the test formula shows the final t-test (3,632) is higher than the value of t-table (2,000). This showed that H0 is rejected and H1 is accepted, students who are taught to use picture series are more effective than conventional way.